Towards a Green Future for Sub-Saharan Africa: Do electricity access and public debt drive environmental progress? - Stephen Kelechi Dimnwobi; Kingsley Ikechukwu Okere; Bernard C. Azolibe; Kingsley C. Onyenwife (African Governance and Development Institute (AGDI), 2023)
The combination of rising debt levels, poor electricity access, and environmental deterioration could threaten the attainment of the Sustainable Development Goals (SDGs). Hence, this inquiry examined the implications of public borrowing and access to electricity on environmental sustainability (proxied by ecological footprint (ECOL)and carbon dioxide (CO2) emissions) in Sub-Saharan Africa (SSA), largely overlooked in the literature. In addition to pre-estimation, diagnostic and robustness checks utilized in the study, the instrumental variable generalized method of moment(IV-GMM) approach is employedto examine annual data from 39 SSA economies between 2005 and 2018. The key findings indicate that public debt negatively influences environmental sustainability in the region, while access to electricity exerts a positive and significant impact on environmental sustainability. The study provides recommendations for SSA policymakers to significantly reduce pollution and protect the environment which is vital for sustainable development.
Keywords: 330; Environmental sustainability; SSA; Public debt; Electricity access; Ecological Footprint; Carbon Emission